Assessment of the capabilities of two polar sPC-SAFT terms through application to measured ketone-alkane phase equilibria data - Cripwell, Jamie Theo (Stellenbosch : Stellenbosch University, 2014)
Thesis (MEng)--Stellenbosch University, 2014.